2020
DOI: 10.1039/d0gc03245j
|View full text |Cite
|
Sign up to set email alerts
|

On the improvement of properties of bioplastic composites derived from wasted cottonseed protein by rational cross-linking and natural fiber reinforcement

Abstract: Biocomposites made entirely by renewable biomass demonstrate excellent mechanical, hydrophobic and thermal properties thanks to rational cross-linking and fiber reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Nowadays, chemical links result in an excellent performance to enhance the interface bond between fibres and matrices. A recent study reported by Yue et al [ 128 ], denoting that the enhancement of mechanical properties such as tensile strength, water resistance capability, and thermal stability derived from wasted cotton-seed protein by rational cross-linking and natural fiber, has improved interfacial bonding forces between the fiber and polymer. Additionally, today’s use of enzymes for surface modification of fibre is rapidly increasing.…”
Section: Prior Studies Of Natural Fiber Polymer Compositementioning
confidence: 99%
“…Nowadays, chemical links result in an excellent performance to enhance the interface bond between fibres and matrices. A recent study reported by Yue et al [ 128 ], denoting that the enhancement of mechanical properties such as tensile strength, water resistance capability, and thermal stability derived from wasted cotton-seed protein by rational cross-linking and natural fiber, has improved interfacial bonding forces between the fiber and polymer. Additionally, today’s use of enzymes for surface modification of fibre is rapidly increasing.…”
Section: Prior Studies Of Natural Fiber Polymer Compositementioning
confidence: 99%
“…When the molar ratio of Ra to NaIO 4 was 1:4, the aldehyde content was the highest after 24 h reaction time. This may be because the molecule of raffinose contains two glucose 6-membered rings and one fructose 5-membered rings, according to the literature, one part of the glucose ring requires two parts of NaIO 4 to completely oxidize (open the ring to form a dialdehyde group) and one part of the fructose ring requires one part of NaIO 4 to completely oxidized [13,17,18]. In the oxidation process, the glucose ring was easily oxidized by sodium periodate, and the ring-opening reaction occurs, and the reaction was faster.…”
Section: Partial Oxidization Of Raffinose By Sodium Periodatementioning
confidence: 99%
“…It would be interesting to understand the mechanism of the reactive dye and four crosslinking agents with cotton cellulose, and analyze the effects of changes in hydroxyl contents in the finishing and dyeing process (Figure 4a-e) [13,17,18]. From the combination mechanism that dyeing and anti-wrinkle finishing agents have a competitive relationship with the hydroxyl groups of cellulose, and the hydroxyl content of cellulose was reduced after the combination [24][25][26][27].…”
Section: Anti-wrinkle Finishing and Dyeing Of The Fabricsmentioning
confidence: 99%
“…Soybean meal (SM), the residue after soybean oil extraction, is a substantial and readily available biomass resource and has shown great potential in the wood adhesive industry due to low price and renewable and highly processable characteristics. , However, the poor water resistance and low mechanical strength of SM usually restricted its application and promotion in wood adhesives. In addition, irregular cracks that appeared in the curing process of SM provided a permeation channel for water molecules, accelerating load transfer capacity and water erosion. , Currently, multiple successful strategies were reported to improve water resistance and mechanical strength of the SM-based adhesive through either filling and reducing the cracks of the adhesive layer via the introduction of rigid nanofillers to establish effective energy dissipation domains , or building dense networks via the addition of cross-linking agents . In the former method, the aggregation of nanofillers was reported to lead to stress concentration, which limited the scope of improvement. , The latter method usually employed a cross-linking agent, aiming to form a strong intermolecular interaction network through the cross-linking reactions with amino, carboxyl, and hydroxyl groups in the SM molecule. , However, the dependence of petrochemical resources and the requirement of the stoichiometric addition of the cross-linker were contrary to the concept of low cost and environmental protection; thus, the discovery of a new strategy to prepare high-performance SM adhesives became particularly crucial.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, irregular cracks that appeared in the curing process of SM provided a permeation channel for water molecules, accelerating load transfer capacity and water erosion. 6,7 Currently, multiple successful strategies were reported to improve water resistance and mechanical strength of the SM-based adhesive through either filling and reducing the cracks of the adhesive layer via the introduction of rigid nanofillers to establish effective energy dissipation domains 8,9 or building dense networks via the addition of cross-linking agents. 10 In the former method, the aggregation of nanofillers was reported to lead to stress concentration, which limited the scope of improvement.…”
Section: ■ Introductionmentioning
confidence: 99%